Sleep fragmentation in critically ill children: a review of contributing factors in the pediatric intensive care unit and neurodevelopmental outcomes - Byeon, Alana GaHyun; Weiss, Shelly K.; Gilfoyle, Elaine; McKinnon, Nicole K. (Frontiers in Sleep, 2025)
Sleep is a critical neurobiological process essential for brain maturation, emotional regulation, cognitive development, and overall organ system homeostasis. In the pediatric intensive care unit (PICU), sleep architecture is frequently disrupted by environmental stimuli, sedation, and clinical interventions, resulting in sleep fragmentation. Unlike sleep deprivation, sleep fragmentation preserves sleep duration but impairs its continuity and depth, disproportionately affecting slow-wave sleep, that is essential for growth, healing, in addition to immune function and REM sleep, that is fundamental for synaptic plasticity, neurogenesis, and memory consolidation. These disruptions are particularly concerning in children, who require more sleep than adults due to ongoing neurogenesis and rapid somatic growth, rendering them uniquely vulnerable to adverse effects. Emerging evidence links fragmented sleep in the PICU to altered neurodevelopmental trajectories and increased risk of Pediatric Post-Intensive Care Syndrome (PICS-p), with delirium serving as a key mediator. Despite promising adult studies on sleep-promoting interventions and EEG-based monitoring, pediatric research remains limited. Future research should prioritize objective sleep monitoring, developmental tailoring of care protocols, and longitudinal studies to clarify the impact of sleep fragmentation on recovery and neurodevelopment. This narrative review highlights the urgent need to recognize and preserve sleep as a modifiable determinant of neurocognitive outcomes in critically ill children.